The Influence of Islamic Character Education Implementation on Students’ Mental Health - Helsa Nasution; M. Agung Rahmadi; Luthfiah Mawar; Nurzahara Sihombing; Ismail Saleh Lubis (Tunjuk Ajar: Journal of Education and Culture, 2025)
Abstract: This study explores the impact of Islamic character education implementation on students’ mental health through a structural equation modeling (SEM) approach. By analyzing meta-data from 38 studies involving a total of 12,467 respondents, the results reveal a significant correlation between Islamic character education and mental health (r = 0.72, p < 0.001). Furthermore, structural model analysis indicates that Islamic character education has a direct effect on mental health (β = 0.58, p < 0.001) and an indirect effect through emotion regulation (β = 0.32, p < 0.01), yielding a total effect of 0.67. Additionally, invariance testing confirms that the model remains consistent across different age groups and genders (CFI = 0.94, RMSEA = 0.048). The SEM results validate the theoretical model’s fit (χ² = 312.45, df = 145, p < 0.001; GFI = 0.93; NFI = 0.92; TLI = 0.95). These findings extend the studies of Naqiyah (2022) and Khodijah et al. (2024), which previously only highlighted direct relationships without considering mediation variables. Furthermore, unlike the study by Yahaya et al. (2012), which found a moderate effect (β = 0.41), this research uncovers a more substantial and comprehensive impact by identifying emotion regulation as a key mediator. Lastly, the findings emphasize that integrating Islamic values into character education plays a crucial role in enhancing students’ mental health and provides new insights for developing Islamic values-based educational strategies.